RELIGIOSITY AND SAVING BEHAVIOR: A PRELIMINARY INVESTIGATION AMONG MUSLIM STUDENTS IN INDONESIA - Alfi, Coky Fauzi; Yusuf, Sharifah Norzehan Syed (Journal of Islamic Monetary Economics and Finance, 2022)
This study examines the relationship between religiosity, saving intention, and saving behavior among Muslim university students in Palembang, Indonesia. A quantitative research approach is employed for this study. We gather data from a total of 103 respondents aged between 18 and 22 years and apply the partial least square path modelling (PLS-PM) technique. We find religiosity to be significantly related to saving intention and behavior. In addition, saving intention and saving behavior are significantly and directly related. Meanwhile, according to Cohen’s convention, the effect size of the association between religiosity and saving intention and behavior is small.